The Fraction Exhaled Nitric Oxide as a Biomarker of Asthma Control. Issue 14 (January 2019) - de Abreu, Fernanda Cruvinel; da Silva Júnior, Jose Laerte Rodrigues; Rabahi, Marcelo Fouad
Introduction and Objective: The main goal of asthma treatment is to achieve and maintain clinical control of the disease. The exhaled fraction nitric oxide (FeNO) level is a biomarker of T-helper cell type 2 (Th2) inflammation of the airways. Our objective was to determine whether the FeNO level can be used to discriminate between patients with controlled, partially controlled, and uncontrolled asthma. Materials and Methods: The FeNO level and asthma control were evaluated in a retrospective and analytic cross-sectional study through data collected from asthmatic patients who were assessed by clinical history, asthma control, physical examination, spirometry, and FeNO level. Asthma control was determined by the criteria of the Global Initiative for Asthma and classified as controlled asthma, partially controlled asthma, and uncontrolled asthma. The FeNO values were classified as low (<25 ppb) or intermediate/high (⩾25 ppb) based on the American Thoracic Society recommendations. Results: The symptoms of 81 asthmatic patients were classified as controlled (34 [42%] patients), partially controlled (27 [33.3%] patients), and uncontrolled (20 [24.7%] patients). The FeNO level discriminated between the uncontrolled and controlled groups ( P  = .01) and between the uncontrolled and partially controlled groups ( P  = .01), but not between the controlled and partially controlled groups ( P  = .98). An FeNO level >30 ppb was associated with uncontrolled asthma ( P  = .0001) with an area under the receiver operating characteristic curve of 0.78 (95% confidence interval = 0.65-0.89). Conclusions: FeNO level could be helpful in determining asthma control as >30 ppb was associated with uncontrolled asthma.